A NIR turn-on fluorescent probe applied in cytochrome P450 reductase detection and hypoxia imaging in tumor cells. (April 2017) - Cui, Lei; Shi, Yanping; Zhang, Shuping; Yan, Luliang; Zhang, Huan; Tian, Zhenran; Gu, Yingying; Guo, Ting; Huang, Junhai
Abstract: In vivo monitoring of the hypoxic area is urgently required. Near infrared (NIR) fluorescence-active fluorophores with excellent photo stability are preferable for in vivo imaging. A novel rational designed turn-on fluorescent probe with high selectivity and long-wavelength was synthesized which was applied in bioreductase (cytochrome P450 reductase which overexpressed in tumor cells) and hypoxia detection. The NIR probe (AZO-DCM ) is based on a photo stability fluorophore dicyanomethylene-4 H -pyran dye (DCM ) with an azo bond as probe quencher and hypoxic trigger. After reacted with cytochrome P450 reductase, azo bond was cleaved andDCM released with fluorescent on. The designed probe showed high anti-interference ability which cannot disturb by many interfering substances, such as biothiols, inorganic salts (included sulfite salt) and amino acid.AZO-DCM performed good selectivity and sensitivity to cytochrome P450 reductase and hypoxia. The fluorescent intensity was increased more than 150-fold after response to cytochrome P450 reductase and NADH system in 4 min. The reaction mechanism also proved by HPLC experiment. ProbeAZO-DCM displayed excellent properties in identifying different hypoxic status of tumor cells in vivo . Graphical abstract: Highlights: ProbeAZO-DCM was a NIR fluorescent probe for cytochrome P450 reductase detection. ProbeAZO-DCM performed good selectivity, high sensitivity and anti-interference to cytochrome P450 reductase under hypoxia. ProbeAZO-DCM displayed excellent properties in identification of different hypoxic status of tumor.